Effect of COVID-19 Self-care Training via Telemedicine on Perceived Stress and Corona Disease Anxiety in Pregnant Women: A Quasi-experimental Study - Motahhare Hashemzahi; Samira Khayat; Somayeh Khazayan (Mashhad University of Medical Sciences, 2022)
Background & aim: The coronavirus pandemic has increased stress and anxiety among pregnant women and established barriers to in-person care around the world. Accordingly, the purpose of this study was to determine the effect of COVID-19 self-care training via telemedicine on perceived stress and corona disease anxiety in pregnant women.Methods: The present quasi-experimental study was conducted on 100 pregnant women who referred to comprehensive health centers in Zahedan, Iran between June and September 2021. The sample was randomly assigned into two groups of 50 subjects. The intervention group received the educational content via WhatsApp Messenger in six sessions. Data collection tools were Perceived Stress Scale (PSS) and Corona Disease Anxiety Scale (CDAS). The self-administered questionnaires were completed before the intervention and one month after the training program.Results: After the intervention, mean PSS score in the intervention group (25.34±6.63) was significantly reduced compared to the control group (28.42±5.75) (p=0.015). Also, mean CDAS score in the intervention group (13.14±7.29) had a significant decrease compared to the control group (20.54±6.67) (P<0.001).Conclusion: The results of our study confirmed the effectiveness of COVID-19 self-care training via telemedicine in reducing the perceived stress and anxiety of pregnant women during the coronavirus pandemic. Therefore, the use of this method in the care of pregnant women is recommended to mitigate stress and anxiety.